A SPATIAL ARCHAEOLOGICAL STUDY OF THE JIRAT AND MUSLIM NOBLES CEMETERY IN LOMBOK - Yusuf, Muhamad Satok (UIN Raden Mas Said Surakarta, 2024)
This study aims to analyze the spatial configuration of nine Muslim noble cemeteries in Lombok, which are divided into separate areas called jirats and cemeteries, where individuals and communities are buried. Spatial archaeology approaches are employed to collect, process, analyze, and interpret data. The study revealed that the Lombok cemetery consisted of headstones, jirat, a pavilion, a fence, a gate, and trees, all of which formed a cohesive cultural area and followed Islamic customs. In Lombok, the jirat is a boundary that separates personal and communal areas designated for the deceased. These areas are determined based on lineage and the level of nobility. Most Muslim noble cemeteries in Lombok exhibit the influence of pre-Islamic and Hindu customs. The northern, north-eastern, and eastern sections of the cemetery hold the highest level of sanctity, reserved for the interment of the most distinguished individuals. The highlands were selected as the primary site for the burial of Muslim nobles in Lombok due to their association with sanctity and the elevation of the deceased's status.